Plant based technology among Adi tribe - Kombong Darang (Dera Natung Government College Research Journal)
The state of Arunachal Pradesh is one of the most diverse states in the country and is one the richest state in India in terms of material culture. The plant based technologies that they produced themselves are made out of natural resources available in their surroundings. Their products are simple but last for years and techniques for making such artifacts are indigenous in nature. They learn craftsmanship orally or just by observing from their parents and grandparents. The study documented many plant based artifacts of the Adi tribe that are made out of forest products especially bamboo, canes, and other plants. Further, the study also aimed at unearthing the kinds of possible threats that arise due to globalization which may affect traditional craftsmanship. The study finds out that most of these artifacts are not in use in their daily life anymore which is a matter of serious concern.